Creating a Next‐Generation System of K–12 English Learner Language Proficiency Assessments. Issue 1 (4th April 2016) - Hauck, Maurice Cogan; Wolf, Mikyung Kim; Mislevy, Robert
Abstract: This paper is the first in a series from Educational Testing Service (ETS) concerning English language proficiency (ELP) assessments for K–12 English learners (ELs). The goal of this paper, and the series, is to present research‐based ideas, principles, and recommendations for consideration by those who are conceptualizing, developing, and implementing ELP assessments for K–12 ELs and by all stakeholders in their education and assessment. We also hope to contribute to the active current discussion in the field on improving the instruction and assessment of EL students as well as contribute to bringing these ideas into practice. This paper articulates a high‐level vision for a next‐generation assessment system serving K–12 English learners with a brief overview of the current state of the art for K–12 ELP assessments and the context of current reforms. In addition, the paper discusses the role of digital technology in next‐generation K‐12 ELP assessment systems, noting the distinct conceptual and practical advantages that digital technology offers in assessing ELP as well as principles for evaluating the potential challenges of implementing a digitally based assessment system against these benefits. A proposed theory of action for K–12 ELP assessment systems is also discussed in this paper. The second paper in the series addressed accessibility issues in the context of ELP assessments for ELs and ELs with disabilities (Guzman‐Orth, Laitusis, Thurlow, & Christensen, 2016), the third paper addressed issues related to summative ELP assessments that emerged from the presentations and discussions at the English Language Proficiency Assessment Research working meeting (Wolf, Guzman‐Orth, & Hauck, 2016), and the fourth paper focused on a key concern within such systems—the initial identification and classification of ELs (Lopez, Pooler, & Linquanti, 2016). Abstract : Report Number: ETS RR‐16–06